Microbes profile from blood stream infection cases and their relationship to those of environment in Neonatal unit (Medical Journal of Indonesia, 2012)
Background: Hospital Acquired Infection (HAI)-Blood Stream infection (BSI) cause considerable morbidity, mortality and health care costs. This study aimed to assess the HAI-BSI in neonates with birth weight 1000-2000 g in Neonatal Unit Cipto Mangunkusumo National Hospital (RSUPNCM), Jakarta, during 4 months period (Oct 2010-Jan 2011), and to review the possibility of sources and transmission of environment microbes to the presence of HAI-BSI in the unit. Methods: Subjects of this study were neonates (birth weight 1000-2000 g) with clinically sepsis and within 48 hours or more being hospitalized, no clearly focal infection detected, with catheter lines. Two blood specimens from two separate venipunctures, drawn simultaneously, were cultivated. Identification and antimicrobial susceptibility tests were performed for each isolates. Cultures from environment in the unit and other suspected clinical specimens were also examined. Results: From 29 neonates with 39 episodes of sepsis, 5 positive isolates from blood cultures were obtained i.e. Enterobacter asburiae (2), Enterobacter cloacae (1), Pseudomonas aeruginosa (1) and Klebsiella oxytoca (1). The laboratory confirmed HAI-BSI was 12.8%, and HAI-BSI rate was 1.46 per 1000 catheter line days during 4 months period (Oct 2010-Jan 2011). Cultures performed for environment specimens gave yield some species which were as those from clinical specimens. Antibiogram analysis showed those of environment isolates i.e E. asburiae and P. aeruginosa shared similarity to those of neonates’ blood isolates. Conclusion: Gram-negative bacteria were responsible to the occurrence of HAI-BSI in the Neonatal Unit RSUPNCM. Despite of low HAI-BSI rate found in this study, analysis of antibiogram profiles of the isolates originated from neonates’ blood and environment strongly suggested that cross infection was present in the unit. (Med J Indones 2012;21:32-7) Keywords: Antibiogram, blood stream infection, hospital acquired infection, neonates